1985
DOI: 10.1177/03331024850050s209
|View full text |Cite
|
Sign up to set email alerts
|

Visual Evoked Potentials and Brainstem Auditory Evoked Potentials in Migraine and Transient Ischemic Attacks

Abstract: A study of brainstem auditory evoked potentials (BAEPs) and pattern reversal visual evoked potentials (VEPs), recorded in intercritical phase, was carried out in 20 subjects (10 suffering from common migraine and 10 suffering from vertebrobasilar TIA) in order to obtain a comparative evaluation of cortical-subcortical functions. The data we obtained demonstrate the presence of BAEPs alterations in patients with previous vertebrobasilar TIA: no abnormalities were found in the migraine group. VEPs parameters are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 11 publications
3
36
0
Order By: Relevance
“…This is consistent with other studies on migraineurs [4,14] and in line with the notion that temporal processing parameters are not altered in migraine [1]. Besides the lack of VEP-habituation our patient showed higher pre-habituation P100-amplitudes during the acute period compared with the follow-up phase.…”
Section: Sirssupporting
confidence: 93%
“…This is consistent with other studies on migraineurs [4,14] and in line with the notion that temporal processing parameters are not altered in migraine [1]. Besides the lack of VEP-habituation our patient showed higher pre-habituation P100-amplitudes during the acute period compared with the follow-up phase.…”
Section: Sirssupporting
confidence: 93%
“…The obtained data demonstrate a delay of peak III of the BAEPs in patients with previous vertebrobasilar TIA. These data show that the study of the BAEPs is useful in evaluating the damage produced by anoxia (Benna et al, 1985). Schwarz et al, 1996 showed prolonged interpeak latencies (I-III, I-V, III-V, IV-V) and delayed absolute latencies of waves II, III, V, and I, at least on one side, in the BAEP.…”
Section: Brainstem Strokementioning
confidence: 65%
“…While some authors observed no abnormalities in brainstem responses [23,25,28], others have described some alterations of brainstem functions in migrainours [7,26,27,[29][30][31]. In this study, we aimed to document if any hearing changes were present in children suffering from migraine during or/and between migraine attacks.…”
mentioning
confidence: 89%
“…Auditory hallucinations, tinnitus, fluctuating hearing loss, phonophobia and sudden deafness are previously reported auditory symptoms [1,5,6,[18][19][20][21][22]. Because of ABR latency variables seem to be a sensitive measures of auditory dysfunction, hearing parameters in migraine has been studied with ABR in the relevant literature [7,13,[23][24][25][26][27][28][29][30][31]. In Table 6, we summarized findings of the studies which evaluate the auditory alterations of migrainours with ABR.…”
mentioning
confidence: 99%
See 1 more Smart Citation